2016
DOI: 10.1186/s13099-016-0142-0
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ promotes gastric lymphoid follicle formation but not gastritis in Helicobacter-infected BALB/c mice

Abstract: BackgroundMouse infection studies have shown that interferon-γ (IFN-γ), a T helper 1 (Th1) cytokine, is required for the development of severe pathology induced by chronic Helicobacter infection. This finding is largely based on studies performed using mice that have polarised Th1 responses i.e. C57BL/6 animals. The current work aims to investigate the role of IFN-γ in Helicobacter-induced inflammation in BALB/c mice which have Th2-polarised immune responses.ResultsAt 7 months post-infection with Helicobacter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…In line with what Bosschem et al. showed for H. suis , Chonwerawong et al . found that the host background has a profound impact on the susceptibility to Helicobacter‐induced pathologies.…”
Section: Helicobacter Felis Infection Of Mice As a Model For Human Hsupporting
confidence: 76%
See 1 more Smart Citation
“…In line with what Bosschem et al. showed for H. suis , Chonwerawong et al . found that the host background has a profound impact on the susceptibility to Helicobacter‐induced pathologies.…”
Section: Helicobacter Felis Infection Of Mice As a Model For Human Hsupporting
confidence: 76%
“…Oral administration of alpha 5 defensin restored eubiosis and showed eradication of H. hepaticus. 38 Helicobacter bilis infection of C3H/HeN mice harboring the altered for H. suis, 34 Chonwerawong et al 46 found that the host background has a profound impact on the susceptibility to Helicobacter-induced pathologies. In a Th2-polarized BALB/c mouse model, the Th1 cytokine IFNγ was shown not to be required for host defense against experimental H. felis infection, although it was important for lymphoid aggregate formation.…”
Section: Pathogenesis Of Non Helicobacter Pylori Helicobacter Infecmentioning
confidence: 99%
“…Several studies with the H . species-infected animal models have demonstrated that IFN-γ can induce the formation of MALT, a precursor lesion of gastric MALT lymphoma [105,106]. However, IFN-γ also exhibits antitumor effects by producing NK cells, differentiating CD4 cells to Th1 cells, and activating the cytotoxicity of CD8+ cells [107,108].…”
Section: Caga and Its Regulated Immune Response In Gastric Microenmentioning
confidence: 99%
“…H felis does not form colonies on culture plates. 34 Although no significant differences in inflammatory responses were observed between WT and Nlrc5 mø-KO mice with H pylori infection, H felis-infected Nlrc5 mø-KO mice developed more severe inflammation and glandular hyperplasia when compared with WT animals (Figure 5C-F). A particularly noteworthy finding was that H felis-infected Nlrc5 mø-KO mice also developed significantly higher numbers of lymphoid structures or follicles within the gastric mucosa (Figure 5C-E), consisting of predominantly B220 þ cell populations and few CD3 þ T cells (Figure 5G).…”
Section: Nlrc5 Regulates Helicobacter-induced Gastric Inflammation An...mentioning
confidence: 91%